1993
DOI: 10.1007/bf00665960
|View full text |Cite
|
Sign up to set email alerts
|

Vascular permeability factor (VPF, VEGF) in tumor biology

Abstract: Vascular permeability factor (VPF), also known as vascular endothelial growth factor (VEGF), is a multifunctional cytokine expressed and secreted at high levels by many tumor cells of animal and human origin. As secreted by tumor cells, VPF/VEGF is a 34-42 kDa heparin-binding, dimeric, disulfide-bonded glycoprotein that acts directly on endothelial cells (EC) by way of specific receptors to activate phospholipase C and induce [Ca2+]i transients. Two high affinity VPF/VEGF receptors, both tyrosine kinases, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
490
0
8

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 781 publications
(502 citation statements)
references
References 62 publications
4
490
0
8
Order By: Relevance
“…The issue of methodological consistency, such as how to sample the heterogeneous cancer, which antibody to use, and how to assess or count the vessels, may hamper the development of vessel density into an established prognostic indicator. The role of angiogenic factors, such as VEGF, that stimulate the formation of new blood vessels, has been well established (33). Since angiogenesis is essential for the growth, invasion, and metastasis of cancers, the stimulatory factors may also serve as prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of methodological consistency, such as how to sample the heterogeneous cancer, which antibody to use, and how to assess or count the vessels, may hamper the development of vessel density into an established prognostic indicator. The role of angiogenic factors, such as VEGF, that stimulate the formation of new blood vessels, has been well established (33). Since angiogenesis is essential for the growth, invasion, and metastasis of cancers, the stimulatory factors may also serve as prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The neovascularization and growth of experimental tumours can be inhibited by treatment with monoclonal antibodies against VEGF (Kim et al, 1993;Asano et al, 1995;Melnyk et al, 1996). Finally, VEGF increases microvascular permeability to macromolecules, thereby leading to fibrinogen extravasation and fibrin deposition, which are important processes in tumour angiogenesis (Senger et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For the s.c. model, tumor size was determined by the formula L(W 2 )/2, with measurements being taken in mm with digital calipers. This yielded tumor volume in mm 3 , which we have determined to be roughly equivalent to tumor weight in grams. When tumors reached a size of between 0.5 and 1 g, the animals were terminated, and tumors collected in formalin.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated, for example, that an increase in cytosolic levels of vascular endothelial growth factor (VEGF) in tumor tissue samples is indicative of poorer prognosis for patients with node-negative breast carcinoma. 1,2 VEGF plays a key role in the process of angiogenesis, 3 and the extent of tumor angiogenesis is now widely accepted as a prognostic factor in several cancer types, [4][5][6][7][8] with higher levels being indicative of more aggressive disease.…”
Section: Introductionmentioning
confidence: 99%